2022
DOI: 10.3390/ijerph19042303
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Brolucizumab and Aflibercept in Patients with Neovascular Age-Related Macular Degeneration

Abstract: Age-related macular degeneration (AMD) is a progressive, chronic disease of the central area of the retina, which, if untreated, leads to blindness. This study aimed to compare the effectiveness of therapy using anti-VEGF drugs, namely brolucizumab and aflibercept, in patients with neovascular AMD (nAMD) during a monitoring period lasting around 20 weeks. The analysis consisted of 40 patients diagnosed with neovascular age-related macular degeneration, with 20 patients receiving aflibercept (Eylea, Bayer) at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…This benefit was also maintained at weeks 44 and 48. These results corroborate previous studies [ 15 , 17 , 19 , 20 ]. The SHRM resolution was comparable for both brolucizumab and aflibercept treated eyes.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This benefit was also maintained at weeks 44 and 48. These results corroborate previous studies [ 15 , 17 , 19 , 20 ]. The SHRM resolution was comparable for both brolucizumab and aflibercept treated eyes.…”
Section: Discussionsupporting
confidence: 93%
“…The HAWK and HARRIER phase 3 trials have shown the non-inferiority of brolucizumab against aflibercept, with more than 50% of patients with nAMD maintaining the BCVA gains on q12w dosing interval throughout the study period of 48-96 weeks [14,15]. In addition, brolucizumab has shown effectiveness in improving visual acuity in several studies [13][14][15][16][17][18][19][20]. However, the treatment for nAMD may respond differently in patients at different stages of the disease [21] as well as the treatment may differ in patients with diverse ethnicity and genetic make-up [4,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Although clinical trials and real-life studies [ 9 , 10 , 11 , 12 ] have reported the efficacy of brolucizumab in nAMD management, response to the treatment in vitrectomized eyes remains to be explored. Barchichat et al [ 13 ] described a case of very severe adverse event after bilateral same-day brolucizumab injections, with progression to blindness.…”
Section: Discussionmentioning
confidence: 99%
“…Brolucizumab (Beovu®), developed by Novartis, is a humanized single-chain variable fragment (scFv) that acts as a VEGF inhibitor. Approved by the US FDA in 2019 to treat neovascular wet AMD, 57 brolucizumab is produced in E. coli cytoplasm as IBs. Developed by Immunocore, tebentafusp (Kimmtrak®) is a bispecific gp100 peptide-human leukocyte antigen (HLA)-directed T cell receptor fusion with the scFv of an anti-CD3 antibody to redirect T cells to tumor cells that was approved by the US FDA in 2022 for the treatment of metastatic uveal melanoma.…”
Section: Production In Escherichia Colimentioning
confidence: 99%